Evaluation of the electrical and dielectric behavior of hybrid materials based on layered zinc hydroxide and benzoate - Ruiz Madronero, Christhy; et al. (Ionics, 2019)
Benzoate anions were immobilized into layered zinc hydroxide nitrate (ZHN) via a soft chemistry method. The hybrid material was characterized by powder X-ray diffraction (PXRD), thermogravimetry (TG/DTA), differential scanning calorimetry (DSC) analysis, Fourier-transform infrared (FT-IR) spectroscopy, and impedance spectroscopy. The expansion of the interlayer space at 20.0 Å confirmed the incorporation of the benzoate forming bilayers into the layered structure. The interaction of the organic molecules occurs through the coordination of the carboxylate group to the Zn+2 atoms in the tetrahedral sites of the layered structure. The conductivity, ε′, and ε″ values of the hybrid materials were reduced five orders of magnitude in comparison with those of the inorganic ZHN host matrix at low frequencies. The results suggest that the solvation process between hydroxyl groups of the layers and adsorbed water molecules contributes in the electric response, whereas an induced dipole interaction describes the dielectric behavior of the hybrid material. The description of the electrical and dielectric properties can open new potentialities of this hybrid material for their possible application in electrochemical devices.<br
Keywords: Hybrid materials . Zinc hydroxide nitrate . Benzoate anion . Conductivity response . Dielectric properties